Replikasi Aplikasi SmartHear Sebagai Media Pembantu Komunikasi Dosen dan Mahasiswa dalam Penyampaian Proses Belajar di Kelas - Dennis Alviandi; Djoni Haryadi Setiabudi (Jurnal Infra, 2018)
There are many disturbance that may occur during the learning process, both internal and external disturbances. Internal disturbance that may occur is the inactivity of a microphone or speakers in the classroom, the phone that accidentally sounds from students or lecturers also become an internal disturbance that may occur. On the other hand, external disturbances that may occur in the classroom are noise or out-of-class activities or there is a vehicle noise disturbing the tranquility. Another problem is when students are left behind in material explanations. Many students are also reluctant to re-ask the lesson that is left to the teacher who then even ask his own friends rather than the lecturers, thus disrupting the concentration of other students.To resolve the issue, an application that replicates the SmartHear application is created. This application can help lecturers and students to improve the quality of understanding during the learning process. The SmartHear app can also help students to record ongoing streaming sessions.Testing is done by trying various Android devices to deliver streaming and receive streaming results. Each android device with the API above 19 already meets the standards in order to run the application but there are other factors such as the size of random access memory (RAM) and the type of processor. This application is also created with a version that will process voice input with generalized maximum a posteriori spectral amplitude (GMAPA) algorithm, but this algorithm can not be processed properly in Android devices due to the lack of computing capabilities that can be done in android devices.